2019
DOI: 10.1016/j.ijid.2019.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Crimean-Congo haemorrhagic fever virus in Hyalomma impeltatum ticks from North Kordofan, the Sudan

Abstract: An evidence for Crimean-Congo hemorrhagic fever virus (CCHFV) was found in Hyalomma impeltatum ticks collected from sheep in North Kordofan in the Sudan. Based on sequencing of the partial segment S, the detected virus belongs to lineage I with closest similarity to CCHFV strains from Senegal. So far, this lineage is unknown in the Sudan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Additionally, in Senegal, R. evertesi evertesi had been found to be a competent vector for CCHFV transmission [ 9 ]. Unlike Ghana [ 28 ], Sudan [ 29 ], and Kenya [ 30 ], CCHFV was not detected in ticks of the Rhipicephalus genus, suggesting different evolutionary pressures may be associated with regional vectors.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in Senegal, R. evertesi evertesi had been found to be a competent vector for CCHFV transmission [ 9 ]. Unlike Ghana [ 28 ], Sudan [ 29 ], and Kenya [ 30 ], CCHFV was not detected in ticks of the Rhipicephalus genus, suggesting different evolutionary pressures may be associated with regional vectors.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Hyalomma marginatum is the most studied and known vector of CCHFV in Europe and Asia where it is responsible of the transovarian and transstadial transmission of the virus, ensuring, therefore, its maintenance in nature ( Spengler et al., 2016 ). In Africa, the virus has been detected on numerous occasions in H. dromedarii, H. truncatum, H. rufipes and H. impeltatum ( Swanepoel et al., 1983 ; Zivcec et al., 2017 ; Chitimia-Dobler et al., 2019 ; Kajihara et al., 2021 ; Schulz et al., 2021 ) but also in non Hyalomma species ( Lule et al., 2022 ). In our study, CCHFV was found in H. truncatum , although at a low infection rate but not in H. rufipes , H. impeltatum , H. nitidum, H. detritum , and H. dromaderii.…”
Section: Discussionmentioning
confidence: 99%
“…In this cross-sectional study, tick specimens were collected from livestock and other domestic animals in the period from January to August 2017, in North Kordofan and Kassala states, Sudan [14]. Samples were collected from three localities in the state of North Kordofan, including Sheikan, Al-Rahad, and Um-Ruwabah, and from five localities in the state of Kassala, namely Aroomah, Wagar, Kassala, West Kassala, and Khashm el Griba (Figure 1).…”
Section: Tick Collection and Identificationmentioning
confidence: 99%
“…Tick-borne pathogens of livestock, such as the causative agents of theileriosis, babesiosis and heartwater, have been circulating on the continent, often with a considerable economic cost [11][12][13]. Additionally, zoonotic TBDs, including rickettsioses, pose a serious public health problem [14,15]. Therefore, a contemporary tick and TBD surveillance is relevant in African countries.…”
Section: Introductionmentioning
confidence: 99%